Quality at the heart of decentralisation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Work continues apace on the decentralisation of CTA s Question and Answer Service (QAS). After the establishment of the Southern African service, and the start of work in Eastern Africa led by the Ugandan National Agricultural Research...